2017
DOI: 10.1016/j.atherosclerosis.2017.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Calcification of the splenic, iliac, and breast arteries and risk of all-cause and cardiovascular mortality

Abstract: Background and aims CVD risks associated with coronary artery calcification (CAC) and aortic calcification (AC) are well known, but less is known about other calcified arteries. We aimed to assess the associations of arterial calcification in the breast, splenic, and internal and external iliac arteries with CVD risk factors and mortality. Methods We conducted a case-cohort study nested in a cohort of 5196 individuals who self-referred or were referred by a health care provider for whole body computed tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 33 publications
0
20
0
3
Order By: Relevance
“…In other solid organ transplants (SOT), increased donor age is associated with worse outcomes . Age has been identified as an independent risk factor for calcification of both the internal and external iliac arteries, and arterial stiffness has been demonstrated to increase with age . A UTx performed during the first German series exemplifies the potential vascular implications of using older donors.…”
Section: Donorsmentioning
confidence: 99%
“…In other solid organ transplants (SOT), increased donor age is associated with worse outcomes . Age has been identified as an independent risk factor for calcification of both the internal and external iliac arteries, and arterial stiffness has been demonstrated to increase with age . A UTx performed during the first German series exemplifies the potential vascular implications of using older donors.…”
Section: Donorsmentioning
confidence: 99%
“…14 Other vascular beds, such as splenic, iliac, and breast arteries, have been studied and continue to add to the growing body of research of calcification and the concept of atherosclerotic burden. 15…”
Section: Introductionmentioning
confidence: 99%
“…20) Therefore, finding a simple and effective marker of arterial stiffness may help reducing cardiovascular morbidity in hemodialysis patients. 21,22) Previous studies have shown that traditional cardiovascular risk factors play some roles in the progression of arterial stiffness before development of ESRD. But the enhanced rate of progression of arterial stiffness in hemodialysis patients was probably determined by more specific nontraditional ESRD-related risk factors such as advancedglycation end products.…”
Section: Discussionmentioning
confidence: 99%